Penatalaksanaan Holistik Pada Tn. B Usia 50 Tahun dengan Ulkus Diabetikum Melalui Pendekatan Kedokteran Keluarga di Puskesmas Rawat Inap Tanjung Sari - Salsabila, Dea Muthia; Zuraida, Reni (CV. Jasa Sukses Abadi, 2024)
Diabetes Mellitus is a metabolic disorder characterized by chronic hyperglycemia. Diabetic ulcer is a state of ulcer, infection, and/or tissue damage, which is associated with neurological disorders and peripheral vascular disease in the lower extremities. The family approach in the management of diabetic ulcers and Diabetes Mellitus helps to identify factors that influence both clinically, personally and psychosocially in the family so that management will be more comprehensive. The purpose of this study was to application of evidence-based medicine-based family doctor services to patients by identifying risk factors, clinical problems, and patient management based on a patient problem-solving framework using a patient-centered and family approach. This study is a case report. Primary data were obtained through anamnesis (autoanamnesis), physical examination, supporting examination and physical environment. The assessment is based on a holistic diagnosis from the beginning, process, and end of the study qualitatively and quantitatively. The patient complained of an open wound on the leg, numbness on both left, frequent urination and easy thirst. The patient has been diagnosed with DM since 2019. The patient was diagnosed with DM based on history, physical examination and supporting examinations. Knowledge of patients and families about the disease they suffer is lacking. After the intervention, the patient showed clinical improvement and there was a change in behavior. In the quantitative assessment, there was an increase in all aspects assessed, namely knowledge, diet and physical activity. Diagnosis and management of these patients is carried out in a holistic and comprehensive manner, patient center, family appropriate with regular DM treatment according to EBM is needed in order to control blood sugar by changing the patient's behavior so as to prevent other complications from arising.